Enhanced expression of L-asparaginase II by fusion of pSSPM3 synthetic promoter into pET-28a+ expression vector for alternative targeted therapy of acute lymphoblastic leukaemia - Aliya, Lisana Shiddiqin; Julizar, Julizar; Rasyid, Roslaili; Pertiwi, Dian; Syukriani, Lily; Nursyafi, Fauzan Syarif; Saibi, Ihsan R. A.; Hasibuan, Imron Martua; Febiona, Keysha Putri; Jamsari, Jamsari (Bioma : Berkala Ilmiah Biologi, 2025)
The use of commercial L-asparaginase II from E. coli and Erwinia chrysanthemi for acute lymphoblastic leukemia (ALL) therapy causes adverse effects (allergic reactions, neurotoxicity), necessitating safer alternatives. Serratia plymuthica UBCF_13, harboring the ansB gene, offers a promising source. This study constructed the recombinant plasmid pET-28a+:pSSPM3:ansB to enhance L-asparaginase II expression in E. coli using the synthetic promoter pSSPM3. Molecular verification confirmed successful steps: promoter fusion (674 bp band), ansB digestion (1,057 bp), gene insertion (1,682 bp), and BL21 transformation. Critically, enzyme activity assays revealed that pSSPM3 did not enhance expression in BL21 (0.519 U/mL), showing significantly lower activity (p<0.05) than native controls (0.621 U/mL) and DH10B transformants (0.636 U/mL). While the functional plasmid establishes a platform for novel enzyme production, the unexpected activity reduction in BL21 and higher yield in DH10B highlight host-promoter compatibility challenges. Further optimization of expression systems, purification protocols, and preclinical validation (cytotoxicity, allergenicity) are essential to advance this recombinant enzyme toward therapeutic and scalable industrial applications for ALL in resource-limited settings.